บทบาทของฝ่ายปกครองในกระบวนการยุติธรรมทางอาญาภายใต้บทบัญญัติของรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2540 - ปองศักดิ์ นันทเสน (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Roles of administrative officers in criminal justice process existed in the past and were deemed as the principal responsibility of Thai civil administration. Subsequently these roles have been changed in both legal and practical realities. Particularly after the promulgation of the Constitution of the Kingdom of Thailand B.E. 2540. Thereafter the roles of administrative officers pertaining to the overseeing and reviewing of the criminal justice administration were mostly transferred to the judiciary and other state organs. Research result reveals that civil administration officers are still appropriate to many tasks of criminal justice administration particularly those that require special administrative experiences such as offenses under the election law, et cetera. Besides, human resource, knowledge and experience in the civil administration are abundant and should not be under utilized. This thesis proposes that the roles of civil administrators in criminal justice process should be maintained, particularly for those tasks which the civil administrators have long been overseen and under their lines of practice, for example. Offenses against public registrations of various kinds. Moreover, in certain cases - such as offenses according to election statutes or drug offenses - where civil administrative officers have already gained experience in both legal and administrative aspects, civil administration officers ought to assist other agencies as well. Finally, administrative officers should continue to be responsible for the administration of justice and ought to play an important role in supporting the process particularly with regard to the upholding of citizen rights under the Construction as it deems appropriate.